2022
DOI: 10.1186/s40463-022-00567-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscope-assisted versus conventional neck dissection in patients with oral cancer: A systematic review and meta-analysis

Abstract: Background Neck dissection is an integral component of the treatment of head and neck cancers. The present meta-analysis aimed to compare the use of endoscope-assisted neck dissection (END) with conventional neck dissection (CND) in the existing English literature. Methods A search of PubMed (MEDLINE), Embase, and the Cochrane Library for articles reporting the results of the two techniques of neck dissection was completed independently by two indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Postoperative morbidity is commonly assessed in studies comparing these two surgical modalities. Recent meta-analyses concluded that there were no differences in the incidence of postoperative complications ( 6 , 7 , 17 ) or length of hospital stay ( 6 , 17 ) between patients undergoing conventional or retroauricular surgery. In our analysis, although without statistical significance, no complications were observed in the RG and 20% of cases in the CG experienced complications These complications negatively impact postoperative evolution, limiting patients’ functionality and QOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative morbidity is commonly assessed in studies comparing these two surgical modalities. Recent meta-analyses concluded that there were no differences in the incidence of postoperative complications ( 6 , 7 , 17 ) or length of hospital stay ( 6 , 17 ) between patients undergoing conventional or retroauricular surgery. In our analysis, although without statistical significance, no complications were observed in the RG and 20% of cases in the CG experienced complications These complications negatively impact postoperative evolution, limiting patients’ functionality and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the retroauricular approach emerged as the most versatile option, as it allows adequate dissection of all levels of the ipsilateral neck ( 2 ). Neck dissection by retroauricular approach has been shown to be similar to the conventional technique in terms of oncological and surgical effectiveness, assessed by the number of retrieved lymph nodes, ipsilateral and regional nodal recurrence rates and the incidence of postoperative complications, however, with a shorter hospital stay ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The oral cavity defect was closed primarily or reconstructed using a local flap or free‐tissue transfer immediately after OSCC tumor excision. Cervical lymphadenectomy, including selective or modified radical neck dissection, was performed simultaneously 16,17 . The final pathological staging was determined by the AJCC staging manual, 8th edition 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Cervical lymphadenectomy, including selective or modified radical neck dissection, was performed simultaneously. 16 , 17 The final pathological staging was determined by the AJCC staging manual, 8th edition. 15 Postoperative radiotherapy or chemotherapy was usually recommended in accordance with National Comprehensive Cancer Network guidelines after our multidisciplinary team discussion.…”
Section: Methodsmentioning
confidence: 99%